Sex disparities in diagnosis of bladder cancer after initial presentation with hematuria: A nationwide claims‐based investigation. Issue 4 (13th November 2013) - Cohn, Joshua A.; Vekhter, Benjamin; Lyttle, Christopher; Steinberg, Gary D.; Large, Michael C.
Abstract : BACKGROUND: Women have disproportionately higher mortality rates relative to incidence for bladder cancer. Multiple etiologies have been proposed, including delayed diagnosis and treatment. Guidelines recommend ruling out malignancy in men and women presenting with hematuria. This study sought to determine the difference in timing from presentation with hematuria to diagnosis of bladder cancer in women versus men. METHODS: This is a retrospective population‐based study examining the timing from presentation with hematuria to diagnosis of bladder cancer, based on data from the MarketScan databases, which include enrollees of more than 100 health insurance plans of approximately 40 large US employers from 2004 through 2010. All study patients presented with hematuria and were subsequently diagnosed with bladder cancer. The primary outcome measure was number of days between initial presentation with hematuria and diagnosis of bladder cancer by sex. RESULTS: A total of 5416 men and 2233 women met inclusion criteria. Mean days from initial hematuria claim to bladder cancer claim was significantly longer in women (85.4 versus 73.6 days, P  < .001), and the proportion of women with >6 month delay in bladder cancer diagnosis was significantly higher (17.3% versus 14.1%, P  < .001). Women were more likely to be diagnosed with urinary tract infection (odds ratio = 2.32, 95% confidence interval = 2.07‐2.59) and less likely to undergo abdominal or pelvic imaging (odds ratio = 0.80, 95% confidence interval = 0.71‐0.89). CONCLUSIONS: Both men and women experience significant delays between presentation with hematuria and diagnosis of bladder cancer, with longer delays for women. This may be partly responsible for the sex‐based discrepancy in outcomes associated with bladder cancer. Cancer 2014;120:555–661 . © 2013 American Cancer Society . Abstract : Multiple etiologies have been proposed for the disparate mortality observed for men and women with bladder cancer, including delay in diagnosis and treatment. In a nationwide claims‐based MarketScan investigation, this study found that women experience significantly longer delays in diagnosis after presenting with hematuria.